As redes do tráfico: drogas ilícitas na fronteira Brasil e Paraguai - Gemelli, Vanderleia (2013)
Itaipu Lake is the main factor that favors the development of drug trafficking on the border between Brazil and Paraguay, whose relevant extension complicates the supervision of official agencies. In this sense, this Master s Thesis is aimed to analyze the flow of illicit drug trafficking on the border between Brazil and Paraguay the ones considered are, specifically, trafficking in marijuana, cocaine and crack, given the constant seizures of these drugs understanding that trafficking is a prerequisite for the formation of illegal geographical networks by territory. Therefore, the methodology used was based on literature readings, in statistics survey on drug trafficking, as well as public policies to combat illicit drug trafficking in Brazil and Paraguay, in the preparation and use of maps to represent the mapping of the border in the light of the subject studied, and fieldwork with interviews and questionnaires. From the results, it is worth noting that, given the existence of numerous routes, it is not possible to define through which ones drugs are transported. Notwithstanding the existence of fixed routes, the activity of illicit drug trafficking shows, through its movement, since the drug producing countries, to the end consumer, a complex illegal network by the territory. The main actors involved in this process include farmers working in the cultivation and processing of drug; individuals carrying drugs; big bosses of trafficking, responsible for coordinating the logistics activity, drug users and agents who are part of the bodies responsible for the repression of illicit activity, representing the State.